1986
DOI: 10.1161/01.cir.74.3.477
|View full text |Cite
|
Sign up to set email alerts
|

Myosin isoenzyme distribution in overloaded human atrial tissue.

Abstract: Using nondenaturing polyacrylamide gel electrophoresis, we have identified two distinct myosin isoenzymes in human atrial tissue that correspond to the V1 and V3 isomyosins found in rat ventricular tissue. Normal left and right atrial appendages have approximately 50% V3. When the left atrium was exposed to hemodynamic overload secondary to mitral stenosis, the percent V3 increased to 77 + 10% (n = 10); exposure to hemodynamic overload secondary to mitral regurgitation caused an increase to 70 14% (n = 6). Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 30 publications
2
4
0
1
Order By: Relevance
“…Here in patients with normal ventricular function, we showed no change in myosin isoform composition in patients with AF in comparison with the NSR group. These results are in agreement with Buttrick et al [18] but differ from the results of Narolska et al [19] where an increase in the percent composition of the b-myosin heavy chain in the AF group was reported. Increases in human atrial b-myosin heavy chain expression have been associated with the hemodynamic stress of mitral valve disease and ventricular dysfunction [9,18,20] and thus may be a factor in these previously reported shifts in myosin isoform expression.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Here in patients with normal ventricular function, we showed no change in myosin isoform composition in patients with AF in comparison with the NSR group. These results are in agreement with Buttrick et al [18] but differ from the results of Narolska et al [19] where an increase in the percent composition of the b-myosin heavy chain in the AF group was reported. Increases in human atrial b-myosin heavy chain expression have been associated with the hemodynamic stress of mitral valve disease and ventricular dysfunction [9,18,20] and thus may be a factor in these previously reported shifts in myosin isoform expression.…”
Section: Discussionsupporting
confidence: 87%
“…These results are in agreement with Buttrick et al [18] but differ from the results of Narolska et al [19] where an increase in the percent composition of the b-myosin heavy chain in the AF group was reported. Increases in human atrial b-myosin heavy chain expression have been associated with the hemodynamic stress of mitral valve disease and ventricular dysfunction [9,18,20] and thus may be a factor in these previously reported shifts in myosin isoform expression. In addition, posttranslational changes in myosin can also affect its function and have been implicated as contributors to the contractile deficit in human, and animal models of myocardial failure.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Buttrick et al (6) reported that there is an increase in the relative amount of the native myosin, V3, which has the MHC-␤ isoform, in the left atrium in association with mitral stenosis. It is possible, therefore, that the higher level of MHC-␤ in women than in men is associated with the greater occurrence of mitral valve stenosis in women, although there is insufficient information to evaluate the extent of stenosis among subjects in the present study and its contribution to the observations.…”
Section: Discussionmentioning
confidence: 99%
“…During the development and the adult, α - MYH is predominately expressed in the atrial chamber and β - MYH in the ventricular chamber in both humans and chicks [2933]. This is further illustrated by the increased expression of β - MHC in the atria of human hearts under pressure overload [34, 35]. MHC analysis of human soleus muscle shows that this muscle expresses an approximately equal mix of type I and IIa isoforms, but the type IIx MHC is not expressed [36].…”
Section: Introductionmentioning
confidence: 99%